Genetic linkage analysis to identify a gene required for the addition of phosphoethanolamine to meningococcal lipopolysaccharide. - Tang, C; Stroud, D; Mackinnon, F; Makepeace, K; Plested, J; Moxon, E; Chalmers, R (2002)
Lipopolysaccharide (LPS) is important for the virulence of Neisseria meningitidis, and is the target of immune responses. We took advantage of a monoclonal antibody (Mab B5) that recognises phosphoethanolamine (PEtn) attached to the inner core of meningococcal LPS to identify genes required for the addition of PEtn to LPS. Insertional mutants that lost Mab B5 reactivity were isolated and characterised, but failed to yield genes directly responsible for PEtn substitution. Subsequent genetic linkage analysis was used to define a region of DNA containing a single intact open reading frame which is sufficient to confer B5 reactivity to a B5 negative meningococcal isolate. The results provide an initial characterisation of the genetic basis of a key, immunodominant epitope of meningococcal LPS.